Organization of educational and developmental training of school students at mathematics lessons - Gabdullin, Rustem; Kozhabaev, Kairzhan; Kostangeldinova, Alma (Opción, 2018)
The purpose of this paper is to highlight the importance of teaching and teaching mathematics in the country and will seek to address the educational weaknesses in this field. The objectives of math education, which include: Educational, cultural and emotional goals, will be discussed in general. This necessity is stipulated by the innovative processes occurring in the educational system of the Republic of Kazakhstan. The results of the research show that students getting the profession of mathematics teachers lack in their training process orientation at the development of schoolchildren’s personal traits.